Is insomnia disorder associated with time in bed extension? - Yoann Birling; Guixia Li; Mingxian Jia; Xiaoshu Zhu; Jerome Sarris; Alan Bensoussan; Jian Wang; Paul Fahey (Sleep Science, 2020)
Objective: There is a lack of evidence for extension of time in bed behaviors (i.e., getting to bed earlier, going out of bed later, staying in bed while awake and napping) as perpetuating factors of insomnia. The aim of this study is to assess if insomnia disorder is associated with extension of time in bed behaviors. Methods: 150 good sleepers and 173 insomniacs were recruited between December 2017 and June 2018. A cross-sectional survey was performed using the Wang Insomnia Integrated Questionnaire. Results: Bedtime, rising time and time in bed were not different between good sleepers and insomniacs (Cohen’s d, <0.01, 0.07, 0.07, respectively; all p>0.05) and were not correlated with insomnia severity (all p>0.05). Staying in bed while awake during the night and in the morning where both different between good sleepers and insomniacs (Cohen’s d, 1.33 and 0.85, respectively; all p<0.001) and were positively correlated with insomnia severity (all p<0.001). Napping was more frequent (p<0.01) among good sleepers (63.3%) than insomniacs (48.6%) and a predictor of good sleep (p<0.01). Conclusion: Going to bed earlier and getting out of bed later do not seem to be associated with insomnia. Staying in bed while awake during the night and in the morning are associated with insomnia but could be only signs of insomnia symptoms. Limiting time in bed to prevent insomnia might and suppressing insomniacs’ napping behavior to treat insomnia might not be effective.